From a Pope’s nightmare, a great public health institution: the Santo Spirito in Saxia Hospital, in Rome (Italian Journal of Public Health, 2010)
Sometimes even bad dreams can have a positive effect on reality. Legend states that Pope Innocent III had a nightmare in which he imagined that fishermen pulling in their fishing nets from the Tiber between the Mole Adriana and the old bridge Neroniano, found the soft little bodies of infants that had been thrown into the river by unfortunate women, eager to suppress the fruits of their sins. Two XV Century frescoes depicting this legend, “Fishing macabre” and “The Dream of Innocent III”, XV Century’s frescoes, can be found in the Sistine Chapel of the Santo Spirito Hospital. The Pope, horrified by his vision, ordered the establishment of a safe haven for girls in need who were without family, the sick, the infirmed and the abandoned. This refuge was established at the Hospital of Santo Spirito in Saxia. Investigating the history of the hospital leads you along a fascinating journey into the history of healthcare in Rome, a journey that helps to explain how Public Health in Italy, and in particular Rome, was founded. Furthermore it explains how health care assistance, funded by charities, both private and religious, developed into the social imperative that it is today guaranteed by the state. The hospital was rebuilt after 1198, when a fire burnt.